USING OF ELECTROSPUN CHROMIUM OXIDE NANPFIBER TO INCREASE THE SHELF LIFE OF FROZEN BEEF BURGER - Majd A. A; Alrubeii, A. M. S.; L. T. Al–Hadedee (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
Electrospun Whey protein membranes reinforced with electrospun chromium oxide nanofibers were utilized for the packaging of beef burger, which were subsequently frozen and stored for 3 months. The chromium oxide nanofibers were incorporated into the membranes at two concentrations 6, 8 %. The study exhibited promising results for the electrospun nanofibers, as their addition contributed to reducing the total bacterial count, psychrophilic bacterial count, and coliform count during the storage period, at both concentrations: 4.89 × 103, 4.36 × 103, 3.28 × 101, 2.48 × 103, and 2.79 × 103 colony-forming units per gram (CFU/g), respectively. Meanwhile, the moisture, protein, fat, and ash percentage of the beef burger reached 60.19, 60.10, 18.41, and 18.49%, respectively, for both additive concentrations. The addition of nanofibers also improved water-holding capacity during storage, reaching 39.02 and 39.63% for the respective concentrations. Moreover, it helped maintain a stable pH level of 5.70 and 5.64 during the final storage period. Additionally, the inclusion of nanofibers ensured that the peroxide value remained within acceptable limits at 7.17 and 6.84 milliequivalents per kilogram, respectively.